Penanganan yang berfokus pada emosi dan ide bunuh diri pada mahasiswa - Mumtaza, Atira; Safira, Annisa; Wulandari, Nabila (UIN Maulana Malik Ibrahim Malang, 2024)
This study investigates the relationship between emotional-focused coping and suicidal ideation in college students. This study aims to understand the extent to which emotion-focused coping skills can influence suicidal thoughts among college students. The research uses a quantitative descriptive method with an instrument in the form of a Likert-scale questionnaire. The research sample involved 101 students from UIN Malang. The results of the analysis show that there is a significant negative relationship between emotional-focused coping and the concept of suicidal ideation, with a coefficient of determination of -0.500. This indicates that 25% of suicidal tendencies can be explained by low emotional-focused coping. Variables measured in emotional control include self-blame, avoidance efforts, and thoughts about desires. Meanwhile, the concept of suicide is measured through fulfilled desires and plans. A total of 30 of the 41 items in this study were considered valid. These findings highlight the importance of understanding emotional-focused coping in efforts to reduce the risk of suicide among students. KEY WORDS: emotional focused coping ; suicidal ideation; student ABSTRAK Studi ini menyelidiki hubungan antara emotional focused coping dan ide tentang bunuh diri pada mahasiswa. Penelitian ini bertujuan untuk memahami sejauh mana kemampuan coping yang berfokus pada emosi dapat mempengaruhi pemikiran bunuh diri di kalangan mahasiswa. Penelitian menggunakan metode deskriptif kuantitatif dengan instrumen berupa kuesioner skala Likert. Sampel penelitian melibatkan 101 mahasiswa dari UIN Malang. Hasil analisis menunjukkan adanya hubungan negatif yang signifikan antara emotional focused coping dan konsep ide bunuh diri, dengan koefisien determinasi sebesar -0.500. Ini mengindikasikan bahwa 25% kecenderungan bunuh diri dapat dijelaskan oleh rendahnya emotional focused coping. Variabel yang diukur dalam pengendalian emosional meliputi kesalahan pada diri sendiri, upaya menghindari, dan pemikiran tentang keinginan. Sementara itu, konsep bunuh diri diukur melalui keinginan dan rencana yang terpenuhi. Sebanyak 30 dari 41 item dalam penelitian ini dianggap valid. Temuan ini menyoroti pentingnya pemahaman tentang emotional focused coping dalam upaya mengurangi risiko bunuh diri di kalangan mahasiswa. KATA KUNCI emotinal focused coping; ide bunuh diri; mahasiswa Copyright ©2024. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0